Are They Radio or Television Programs? A Case Study from Japan on the Audiovisual Representations of NHK Archives - Ota, Nanako (Unlocking Television Archives in the Digital Era. 16th Media Mutations International Conference, 2026)
NHK (Nihon hōsō kyōkai), the Japanese public broadcasting monopoly, established and manages what is currently Japan’s largest online digitized media archive: NHK Archives. When a user accesses a radio program from NHK Archives, however, they discover an unexpected audiovisual experience. A relevant television program, film, or static image is automatically displayed along with the radio broadcast. This media synergy challenges archival approaches that rely exclusively on a single medium. The NHK Archives’ current representations of radio sound recordings complicate our use of archival sources by combining original audio with visual sources selected through a contemporary post-production editing process. On the one hand, the Archives allow a user to see an audio recording’s historical, political, or cultural significance. At the same time, however, the Archives may misinform the user of how the original audio was heard by the listeners back in time. This paper examines radio programs broadcast during World War II and in the immediate post-war period. These programs are worth analyzing because they were important in and of themselves, but now have altered meanings in the digital environment with the new audiovisual representations.